Modeling and bifurcation analysis of an intraguild predation system - Tua Agustinus Tamba (International Journal of Advances in Applied Sciences, 2023)
This paper proposes a mathematical model of an asymmetric intraguild (IG) predation system with an exclusive alternative resource. In particular, this paper analyzes the effects that the exclusive alternative resource has on the consumption/predation behaviors of both the IG predator and IG prey species in the system. The results presented on this paper show that, if the IG predator is less competitive in consumption and less efficient in conversion of the shared resource than that of the IG prey, then there exists a lower bound on the value of the predation rate parameter that should be maintained by IG predator species to ensure its survival and co-existence in the system.